Behavioural avoidance and enhanced dispersal in neonicotinoid‐resistant Myzus persicae (Sulzer). Issue 1 (29th May 2013) - Fray, Lucy M; Leather, Simon R; Powell, Glen; Slater, Russell; McIndoe, Eddie; Lind, Robert J
Abstract BACKGROUND The peach potato aphid Myzus persicae is a major agricultural pest capable of transmitting over 100 plant viruses to a wide range of crops. Control relies largely upon treatment with neonicotinoid insecticides such as thiamethoxam (TMX). In 2009, a strain denoted FRC, which exhibits between 255‐ and 1679‐fold resistance to current neonicotinoids previously linked to metabolic and target site resistance, was discovered in France. Dispersal behaviour may potentially further enhance the resistance of this strain. This study investigated this possibility and is the first to compare the dispersal behaviour of aphid clones of the same species with differing levels of neonicotinoid resistance. RESULTS Comparing the dispersal behaviour of the FRC strain with that of a clone of lower neonicotinoid resistance (5191A), and a susceptible clone (US1L) highlighted several differences. Most importantly, the FRC strain exhibited an increased ability to locate untreated areas when presented with an environment consisting of both TMX‐treated and untreated plant tissue. CONCLUSION The altered dispersal behaviour of the FRC may partially account for the high level of neonicotinoid resistance exhibited by this strain in the field. Since the dispersal of aphid vectors is key to the transmission of viruses across crop fields this has implications for current crop protection practice. © 2013 Society of Chemical Industry